Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/2325967117752105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Workload on the Evolution of Hip Internal and External Rotation in Professional Baseball Players Over the Course of the Season

Abstract: Background:Although restricted hip range of motion (ROM) is associated with an increased risk for injuries in baseball players, the evolution of hip ROM over the season remains undefined.Hypothesis:Hip ROM profiles would be symmetric between hips and positions (pitchers vs position players) but would decrease from preseason to postseason. Additionally, it was hypothesized that this decrease in motion would correlate with workload.Study Design:Cohort study; Level of evidence, 2.Methods:Bilateral hip ROM was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…The findings of hip ROM decreasing over the season for pitchers and position players are consistent with the literature. Camp et al 7 reported that pitchers and position players lost 6° of lead hip TROM from pre- to postseason. Furthermore, the authors found a correlation between loss of hip IR in pitchers and increased pitches thrown and innings pitched.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of hip ROM decreasing over the season for pitchers and position players are consistent with the literature. Camp et al 7 reported that pitchers and position players lost 6° of lead hip TROM from pre- to postseason. Furthermore, the authors found a correlation between loss of hip IR in pitchers and increased pitches thrown and innings pitched.…”
Section: Discussionmentioning
confidence: 99%
“…Youth pitchers have also been found to have correlations between hip ROM and cumulative years played, seasonal pitch volume, and months played in the past year [11]. Thus, allowing researchers to conclude that overall de-creased hip ROM may negatively impact pitching mechanics, performance, and increase injury risk [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown alterations in bilateral shoulder and hip ROM and strength over not only a competitive baseball season but also following single pitching bouts [10,12,[24][25][26]. Though data regarding hip and shoulder strength adaptations over the course of…”
Section: Introductionmentioning
confidence: 99%
“…In general, symmetric HRMs have been observed for both hips and across positions during preseason medical checkups of adult baseball players. 4,10,39 However, previous studies have also revealed significant differences between HRM variables in pitchers and position players. 4,25,39 Laudner et al 25 and Sauers et al 39 reported that position players had significantly more HIRs than pitchers; however, Camp et al 4 reported the opposite results.…”
Section: Discussionmentioning
confidence: 94%